Appropriation and Commodification of Cultural Heritage: Ethical and Intellectual Property Issues to Consider (Fact Sheet) - Marina La Salle; Commodifications of Cultural Heritage Working Group (Simon Fraser University, 2014)
The IPinCH Fact Sheet initiative aims to provide information and guidance on important issues emerging in cultural heritage research. RESOURCESDeclarationsReportsPublicationsPresentationsVideosPodcastsFact SheetsTeaching ResourcesReading ListsLinks